Micro Credit And Economic Development - Rajkumar, R; Indian Economic Association. Annual Conference 2007 : Srinagar, India); Rajkumar, R.; Singh, Sita Ram, 1950- (New Delhi : Regal Publications, 2010)
Papers presented at the 90th Annual Conference of the Indian Economic Association, held at Srinagar during 27-29 December 2007.
Includes index.
Includes bibliographical references.
Keywords: Microfinance -- India -- Congresses; Rural development -- India -- Congresses; Women in development -- India -- Congresses; Poverty -- Government policy -- India -- Congresses; Rural credit -- India -- Congresses